Report of the Working Group on Agricultural Research and Education for the Tenth five Year Plan (2002-2007) - Planning Commission (Planning Commission, 2002)
1966-67 to 1980-81 when adequate food grain production was achieved by recognizing and introducing the role of science and technology in agriculture, reorganisation of the Indian Council of Agricultural Research, establishment of new organisation and institutions such as The National Dairy Development Board, The National Seed Corporation of India, The Food Corporation of India, Fertilizer Industry, State Agriculture Universities and others by the Government of India. This was the period in 1966-67 when policies for procurement of food grains, buffer stock and public distribution system were put in place along with the Commission On Cost and Price in agriculture (Agriculture Price Commission).
Government of India Planning Commission
Government of India Planning Commission